The Effectiveness of Tomato Fruit Antioxidant Handbody Lotion - Ariyanti Ariyanti; Eni Masruriati; Dwi Setyowati; Filza Mazaya Nurulita (GLOBAL HEALTH SCIENCE GROUP, 2022)
Antioxidants are found in various types of fruits and vegetables, one of which is tomatoes ( Licopersicon esculentum Mill ). Tomatoes contain lycopene, flavonoids and vitamin C compounds as antioxidants. Tomato fruit is made into juice by using the extraction method. Tomatoes with direct use are less effective, so they are made in the form of pharmaceutical preparations in the form of hand body lotion gel using tomato juice. The purpose of this study was to determine the effectiveness of tomatoes as antioxidants in handbody lotion gel preparations using the DPPH method. This research used experimental research method with 3 concentration formulas of tomato juice handbody lotion, namely 5%, 10% and 15%. The physical evaluation test showed that the results had met the physical requirements of the handbody lotion (organoleptic, homogeneity, spreadability, adhesion, viscosity, pH, lotion type and hedonic test). The results showed that tomatoes have effectiveness as antioxidants. This test was carried out using the DPPH method on the preparation of handbody lotion gel tomato juice formula II, the IC50 was 6,620 g/mL, which was greater than formulas I and III. The smallest IC50 value was obtained from formula III, which was 5,205 g/mL. The smaller the IC50 value, the stronger the antioxidant power.